Simultaneous Effects of Thermal Radiation and Chemical Reaction on Hydromagnetic Pulsatile Flow of a Casson Fluid in a Porous Space - KUMAR, Challa Kalyan; SRINIVAS, Suripeddi (Engineering Transactions, 2017)
In the present study, the hydromagnetic pulsating flow of Casson fluid between two parallel plates in a porous space, thermal radiation and chemical reaction are investigated. The analytical solutions for flow variables are obtained by using a perturbation technique. The effects of pertinent parameters on velocity, temperature, concentration, Nusselt number and Sherwood number distributions are studied in detail.